How to find a gold on the touristic path – a gold-mining in the Tatra Mts. - Gawęda, Aleksandra (Geotourism/Geoturystyka, 2025)
Gold mineralization is known in the Tatra Mts from the 15th century. The historical mining places could be indentified along the present-day touristic paths, which were used in the past as miner’s roads. Both gold occurrence and genetically connected antimony mineralization are located in the flat-lying mylonitic zones, dipping 5–100 to NW, cutting the Tatra granite. Mylonites are mineralized by quartz and albite. The famous gold-mining galleries are known from Krywań Mt., where gold and antimonite could be found inside quartz veins straight on the touristic path until now. The important sources of gold were also the secondary fluvioglacial deposits. Gold from the Tatra Mts, regardless its origin – both primary and secondary – is of good quality, with Ag content in the range of 1.2–14.8 wt.%. Locally the veinlets of electrum are also observed. Gold in the Tatra Mts. is associated with antimonite. Its crystals are usually coated with secondary antimony oxides and hydroxides. The historical gold-mining places could be of special importance for geotouristic purposes, as they bring the information about both histories of human mining activity in the mountains and about the geological processes, forming the ores, which released the people’s strongest emotions for a few thousand years.